A PROPAGANDA NA ERA DA CONVERGÊNCIA Um estudo comparativo da linguagem publicitária audiovisual nos meios internet e televisão. - Silva, Matheus Berto da (2013)
Since its inception the internet has received by advertisers replicas advertising content developed for other media, but over the years the internet has gained space and received the attention of advertisers eager to use their strengths to benefit from the sale of their products. Yet very little is known about the characteristics of specific language of the internet, and the existing literature is few and inconclusive. Based on this framework study compared the advertising videos developed specifically for the internet with other developed originally for television and published on the Internet in order to identify points of parity and convergence between them with regard to language. The work was based on the theories of cyberculture and the Network Society and the studies of Marshall McLuhan and a comparative analysis of the videos investigated in order to understand the technical language, visual and discursive them. The survey showed marked differences between the two groups of videos investigated, especially with regard to interactivity, and maximizing potential viralization viewing. It also identified that in regard to technical language discourse videos showed little differentiation because the technology and the language used in its construction are the same.